A functional perspective of nematode assemblages as proxy of quality in tropical estuarine tidal flats. (April 2023) - Justino, Juciélia Tenório; Demetrio, Guilherme R.; Neres, Patrícia Fernandes; Meneses, Diógenes; Pinto, Taciana Kramer
Abstract: Functional aspects of biological communities influence ecosystem processes and it is urgent to understand how human disturbances affect functional diversity and ecosystem functions and services. Our purpose was to address the use of different functional metrics of nematode assemblages to evaluate the ecological status of tropical estuaries subjected to different human activities, aiming to advance and improve the knowledge about the usefulness of functional attributes as indicators of environmental quality. Three approaches were compared: functional diversity indexes, single trait, and multi traits using the Biological Traits Analysis. The RLQ + fourth-corner combined method was used to identify relationships among functional traits, inorganic nutrients, and metals concentrations. Lower values of FDiv, FSpe, and FOri indicate a convergence of functions, characterizing impacted conditions. A dominant set of traits was related to disturbance, mainly inorganic nutrient enrichment. All the approaches allowed for the detection of disturbed conditions, however, multi traits was the most sensitive one. Graphical abstract: Image 1 Highlights: Different sets of nematode traits were related to different inorganic pollutants. Multitraits analysis was the most efficient approach detecting disturbed estuaries. Nematodes functional dispersion was not linked to estuaries ecological conditions. Low functional divergence, specialization, and originality may indicate human impacts.